2015
DOI: 10.1186/s12974-015-0342-4
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRα1-mMOG-35-55 treatment of experimental autoimmune encephalomyelitis reduces CNS inflammation, enhances M2 macrophage frequency, and promotes neuroprotection

Abstract: BackgroundDRα1-mouse(m)MOG-35-55, a novel construct developed in our laboratory as a simpler and potentially less immunogenic alternative to two-domain class II constructs, was shown previously to target the MIF/CD74 pathway and to reverse clinical and histological signs of experimental autoimmune encephalomyelitis (EAE) in DR*1501-Tg mice in a manner similar to the parent DR2β1-containing construct.MethodsIn order to determine whether DRα1-mMOG-35-55 could treat EAE in major histocompatibility complex (MHC)-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…A new bioengineered protein comprised of the human leukocyte antigen (HLA)-DRα1 domain linked covalently to mouse MOG-35-55 peptide (DRα1-MOG-35-55) has been shown to modulate monocyte response 206 , 207 and improve histological and clinical outcomes after TBI. 208 …”
Section: Immunotherapy At the Innate Immune Response After Cns Injurymentioning
confidence: 99%
“…A new bioengineered protein comprised of the human leukocyte antigen (HLA)-DRα1 domain linked covalently to mouse MOG-35-55 peptide (DRα1-MOG-35-55) has been shown to modulate monocyte response 206 , 207 and improve histological and clinical outcomes after TBI. 208 …”
Section: Immunotherapy At the Innate Immune Response After Cns Injurymentioning
confidence: 99%
“…Moreover, injection of a MIF antagonist peptide into the spinal cord reduces expression of proinflammatory genes and is neuroprotective in a model of encephalomyelitis (60). These data suggest that MIF elicits its pathological functions in the spinal cord by activation of proinflammatory mechanisms which may induce profound neurotoxic effects in the spinal cord (61).…”
Section: Discussionmentioning
confidence: 92%
“…However, there were also studies demonstrating the limitation of the application of interferon-β in the treatment of the multiple sclerosis or EAE, showing that interferon-β therapy was effective against multiple sclerosis or EAE only in the NLRP3 inflammasome-dependent EAE ( Inoue et al, 2012 ; Inoue et al, 2016 ). In addition, Benedek et al (2015 , 2017 ) demonstrated that DRα1-mouse(m)MOG-35-55, a less immunogenic alternative to two-domain class II construct developed by their lab, significantly reversed the clinical and histological symptoms of EAE mice through the inhibition of the NLRP3 inflammasome targeting on the MIF/CD74 pathway. Moreover, previous studies in our lab also reported several effective NLRP3 inflammasome inhibitors in the treatment of EAE.…”
Section: Nlrp3 Inflammasome In Cns Disordersmentioning
confidence: 99%